Ion-beam synthesis and photoluminescence of SiC nanocrystals assisted by MeV-heavy-ion-beam annealing - Khamsuwan J. (2014)
This work explored a novel way to synthesize silicon carbide (SiC) nanocrystals for photoluminescence. Carbon ions at 90 keV were implanted in single crystalline silicon wafers at elevated temperature, followed by irradiation using xenon ion beams at an energy of 4 MeV with two low fluences of 5 × 1013 and 1 × 1014 ions/cm2 at elevated temperatures for annealing. X-ray diffraction, Raman scattering, infrared spectroscopy and transmission electron microscopy were used to characterize the formation of nanocrystalline SiC. Photoluminescence was measured from the samples. The results demonstrated that MeV-heavy-ion-beam annealing could indeed induce crystallization of SiC nanocrystals and enhance emission of photoluminescence with violet bands dominance due to the quantum confinement effect. © 2011.